2017
DOI: 10.1002/bkcs.11081
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of η–Al2O3 by SiO2 Impregnation to Enhance Methanol Dehydration Activity

Abstract: Silica impregnated η‐Al2O3 catalysts (Si(number)Al) were prepared for methanol dehydration, with the number indicating the Si wt % added to η‐Al2O3. The Si(0.25)Al and Si(0.50)Al catalysts with the greatest number of acid sites had the highest methanol dehydration activities among the prepared catalysts. Si addition up to 0.5 wt % increased the number of the acid sites, which was slightly decreased by further Si addition. The number of weak acid sites correlated well with the catalytic activity for methanol de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…The new Bronsted acid sites were generated by the introduced SiO 2 layer. This is reinforced by the results reported by Jo et al 43 where new Bronsted acid site generation was identified when SiO 2 was introduced onto the pure η-Al 2 O 3 support. Meanwhile, in the wavenumber range between 3500 and 4000 cm −1 , a new inverted peak was observed at ca.…”
Section: Other Physiochemical Properties 331 Py-driftsupporting
confidence: 53%
See 2 more Smart Citations
“…The new Bronsted acid sites were generated by the introduced SiO 2 layer. This is reinforced by the results reported by Jo et al 43 where new Bronsted acid site generation was identified when SiO 2 was introduced onto the pure η-Al 2 O 3 support. Meanwhile, in the wavenumber range between 3500 and 4000 cm −1 , a new inverted peak was observed at ca.…”
Section: Other Physiochemical Properties 331 Py-driftsupporting
confidence: 53%
“…Acid sites on the surface may significantly influence the performance of the active-metal components on a catalyst. , Pyridine is often used as the probe molecule in investigating the surface acid sites on a catalyst by IR spectroscopy. Chemisorption of pyridine on Brönsted acid site leads to an IR peak at 1540 cm –1 which is assigned to the ring deformation vibration of pyridine. , Meanwhile, chemisorptions of pyridine on Lewis acid sites show a peak at 1450 cm –1 which is assigned to the deformation vibration of C–H bonds. DRIFT spectra of the Pt/Al 2 O 3 and 9c-SiO 2 /Pt/Al 2 O 3 catalysts after pyridine adsorption are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, copper was used to prevent the strong binding of H 2 O–Al 2 O 3 by enhancing the surface hydrophobicity with CA = 12° for 6% Cu/Al 2 O 3 catalyst that was used for the MTD reaction . Jo et al reported that the addition of Si to η-Al 2 O 3 by using TEOS (tetraethyl orthosilicate) enhanced the MTD conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, catalytic cracking of naphtha represents one of the potential alternatives, due to its advantage in energy consumption, CO 2 emission, and product distribution compared to conventional steam cracking process . To maximize the propylene yield, ZSM‐5 is a common active catalyst studied for naphtha cracking or related subjects, for its high selectivity due to the particular three‐dimensional medium‐sized channel topology …”
Section: Introductionmentioning
confidence: 99%